Implementasi Pembukuan Sederhana Dalam Upaya Peningkatan Produktivitas Kain Songket Tenun Medan - Raya Puspita Sari Hasibuan; Anggiat Situngkir; Darmawati Simanjuntak (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2022)
The impact of the COVID-19 pandemic has caused several Micro, Small and Medium Enterprises to decrease their production due to decreased demand from customers, one of which is our Service partner. Through this service, we hope that we can help our partners in overcoming production problems as well as in terms of bookkeeping. In this service activity the Service team has visited the Service partner to gather information regarding the main needs in the production process to sales, and the result is that the Service team donated equipment in the form of a high-speed sewing machine as much as 1 (one) unit to partners, the sewing machine can be used in production activities, previously in production our partners used the manual method, so with the help of this machine it is possible to increase the production capacity of partners. The method used in this service activity is a visit, on the first visit the Service team explores information related to business development and the obstacles or problems faced so far, then the Service team carries out service activities that answer the problems or constraints described by partners, the distribution of grants in the form of 1 unit of high speed sewing machine and assistance in simple bookkeeping procedures is a solution to the problems or obstacles experienced by partners so far. The Devotion Team hopes that partners will be better in running Micro, Small and Medium Enterprises. The real evidence from the work of 1 unit of high speed machine is the increase in production capacity to double before only being able to produce 10 units of production per day after the addition of a high speed sewing machine, production to 20 units per day and what's interesting is that our partners have implemented simple bookkeeping adequate and appropriate